AB0215 Experimental neuropsychiatric lupus induced by 16/6 idiotype antibodies. (23rd January 2014) - Kivity, S.; Katzav, A.; Teresa-Arango, M.; Rabi, M.; Zafrir, Y.; Agmon-Levin, N.; Blank, M.; Mozes, E.; Chapman, J.; Shoenfeld, Y.
Abstract : Background: The 16/6 idiotype was shown to induce experimental lupus in naïve mice 1 . Its ability to induce brain specific disease was not evaluated before. Objectives: We assessed the behavior and brain immunohistochemistry of naive mice injected intra-cerebra-ventricularly (ICV) with the 16/6 antibody. Methods: Twenty one CH3 mice were injected ICV to the right hemisphere: 11 with human 16/6 idiotype antibodies and 10 with commercial human IgG antibodies (control). Depression was addressed by forced swimming test (FST), explorative activity was evaluated by the staircase test. Cognitive function was examined in the novel object recognition (NOR) and Y-maze tests at days 19 and 20 respectively. Fixated brain sections (50πl thick) were stained for activated microglia, neuronal nucleus, and astrocytes. Results: In the NOR test there was a significant preference for the novel object in the control group (64% time spent near the novel object, p=0.01) and no difference in the preference was seen in the 16/6-injected mice. The preference for spatial novelty in the Y-maze test was significantly higher in the control group compared to the 16/6-injected mice (42% vs. 9% respectively, p=0.06). Depression–like and explorative behavior was not significantly different between 16/6-injected and control mice. Immunohistochemistry analysis revealed increased microglial activation in the hippocamppal, dentate and amygdale regions, in the 16/6 injected group, compared to the control ones. Conclusions: Passive transfer of 16/6 antibodies to mice brain results in a cognitive impairment, and evidence of brain inflammatory changes. This finding may shed light on the pathophysiology of neuropsychiatric lupus. References: Blank, M. and Y. Shoenfeld, The story of the 16/6 idiotype and systemic lupus erythematosus. Isr Med Assoc J 2008; 10(1): p. 37-9. Disclosure of Interest: None Declared